Concentrative (Sahaj Samadhi) meditation expands subjective time. Issue 1 (20th February 2019) - Singh, Amrendra; Srinivasan, Narayanan
Abstract: Previous studies have demonstrated the effect of mindfulness meditation on subjective experience of time. Task difficulty influenced subjective experience of time with larger subjective expansion of time among meditators with a more difficult task. It is not clear whether the effect would generalize to concentrative meditation training. Hence, in the present study, using a temporal bisection task, we investigated the effect of task difficulty (with two discrimination ratios of short and long durations) on subjective experience of time in long‐term concentrative (Sahaj Samadhi) meditators and non‐meditators. The results provide evidence for subjective expansion of time among long‐term concentrative meditators, which is in line with the previous findings with mindfulness meditators. Similar to the earlier study with mindfulness meditators, we also found expansion of time for concentrative meditators only in the difficult task condition where attentional demands are high and less attentional resources are available for processing time. The findings suggest that subjective expansion of time is most likely a general effect of attentional enhancement irrespective of the type of meditation practice.